Case Report: Castleman Disease With an Associated Stromal Spindle Cell Proliferation, PDGFRB Mutation and p53 Expression: Clonal Origins of a Rare Disease - Singh, Kunwar I.; Gollapudi, Sumanth; Kumar, Jyoti; Butzmann, Alexandra; Small, Corinn; Kreimer, Sara; Saglam, Emine Arzu; Warnke, Roger; Silva, Oscar; Ohgami, Robert S. (Frontiers in Oncology, 2022)
Castleman disease (CD) is a rare lymphoproliferative disorder with distinct clinical subtypes. However, our understanding of the underlying pathogenesis of particular subtypes of CD remains unclear. While the characteristic morphologic changes within UCD, including occasional cases of overgrowth of spindled stromal and follicular dendritic cells have been described, the nature and origin of these spindle cells remain elusive. Few reports have suggested that underlying stromal cells in UCD are clonally neoplastic and may be of fibroblastic reticular cell (FRC) or follicular dendritic cell (FDC) origins given their close clonal relationship. Although certain histomorphologic features may aid diagnosis, there are no specific biomarkers that can differentiate a reactive process mimicking UCD from true UCD. Hence, we describe an index case with morphology consistent with the hyaline vascular subtype of UCD with concomitant atypical smooth muscle actin (SMA)-positive stromal spindle cell proliferation containing a recurrent PDGFRB N666S mutation and upregulation of p53 expression. Further analysis of 21 additional cases of UCD identified increased p53 expression by digital image analysis and SMA positive stromal cells predominantly within the paracortical and intrafollicular areas further strengthening the hypothesis of the stromal cellular derivation and origins of UCD.